Targeting and informal insurance - Ethan Ligon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The standard method of testing for efficient risk-sharing in village economies does not allow one to identify vulnerable households, only to make statements about the average risk in the village, or of sub-groups identifiable on the basis of observables. Here, by working directly with inter-household consumption correlations we are able to identify households, which are probably exposed to unusually high amount of idiosyncratic risk. An obvious use for this identifying information involves targeted interventions to help those households. However, the effectiveness of these interventions depends on the market imperfections which exposes those households to idiosyncratic risk to begin with. Using data from the Indian ICRISAT villages, we trace out the expected outcomes of targeted income transfers given several different hypotheses regarding why some households bear idiosyncratic risk. – targeting ; informal insurance ; risk
Keywords: I32; O1; D80; 330; Dorfwirtschaft; Armut; Risiko; Theorie